Examining public perceptions of CSR in sport. (21st September 2018) - Kim, Joon Kyoung; Overton, Holly; Hull, Kevin; Choi, Minhee
Abstract : Purpose: The purpose of this paper is to investigate how the public views two corporate social responsibility (CSR) initiatives practiced by a Major League Baseball (MLB) team. This study examined the role of perceived fit between an MLB team and its two CSR initiatives in shaping consumers' intentions to support the team's CSR efforts. Design/methodology/approach: A between-subjects experiment ( n =207) was conducted using Amazon's Mechanical Turk to examine the impact of CSR fit on consumers' patronage intentions. Findings: The results of this study showed that consumers' perceived fit between sports teams and their CSR has a positive impact on consumers' patronage intentions. The values-driven and strategic-driven attributions of the team's CSR initiatives were positively associated with their patronage intentions. Research limitations/implications: Both the values-driven and strategic-driven attributions were positively associated with consumers' patronage intentions, while previous studies suggested negative association between strategic-driven attributions and consumer behaviors. The findings indicate that consumers do not view professional sports teams' strategic-driven CSR initiatives to be negative business practices. This could result from the fact that CSR initiatives have become a prevalent and expected organizational practice. Originality/value: This study contributes to the literature of CSR within the context of professional sports teams as corporations. The findings of this study suggest that professional sports teams could benefit from CSR initiatives when the teams select social causes with which consumers could infer values-driven and strategic-driven attributions.